Korelasi Lama Senam Asma dengan Faal Paru pada Pasien Asma yang Mengikuti Senam Asma - Eka Bebasari; Miftah Azrin (Jurnal Ilmu Kedokteran, 2016)
Asthma is a chronic inflammatory disorder of the airways. Asthma gymnastics is one of rehabilitation efforts that mayimprove asthma patients lung function. This research was a cross sectional study to determine correlation of durationof asthma gymnastics with pulmonary function. Respondents were all asthma patients who follow asthma gymnasticsin Riau University Teaching Hospital and Health Center Rumbai. Data were collected with spirometry test with totalsampling. Most of respondents were in the age group 41-50 years (38.7%), female respondents 77.4%, most ofrespondents had a history of asthma in the family (61.3%), duration of asthma gymnastics more than 3 months(61.3%), asthma degree was intermittent (38,7%), level of asthma control was controlled 61.3% and spirometry testshowed that 54.8% respondent were classified obstructive. There is a moderate positive correlation between durationof asthma gymnastics with lung vital capacity with r = 0,451 and p = 0,011.